Problem Based Learning Assisted by Mobile Learning to Improve Conceptual Understanding of Primary School Students - Rohmah, Fitriya; Eko Pramono, Suwito; Yusuf, Amin (Educational Management, 2020)
Learning inside of classroom is only merely transferring knowledge or memorizing in nature. It has not had purpose to improve students’ conceptual understandings. To make learning process capable in improving conceptual understanding, teachers should prepare innovative learning model and make their students able to determine solution by themselves from the given problems. This research aims to analyze improvement of students’ conceptual understanding after being intervened by Problem Based Learning assisted by Mobile Learning. This quasi experimental research used nonequivalent control group design. It was done for V graders of Public Primary School 2 Ngeling and Public Primary School 3 Ngeling in Jepara municipality. Techniques of collecting data were documentation, observation, conceptual understanding test in the form of multiple choices. The data was analyzed by gain score test and t-test. The results showed there was significant difference of the students’ conceptual understandings intervened by PBL assisted by mobile learning media. There was significant difference of conceptual understanding score between both groups with significant level 5% with N-gain of experimental group 0.61, categorized as moderate while the control group obtained 0.19, categorized as low. The independent test stated there was difference between both groups as shown by score of tcount 0.411 with significant level 0.000. It showed that problem based learning assisted by mobile learning media could improve the students of the primary schools’ conceptual understandings.